Reading Comprehension Strategies in EFL Classrooms: A Cognitive and Sociolinguistic Approach in Indonesian Schools - Utami, Ema; Rahmat, Rahmat (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2023)
This study analyzes students’ reading comprehension strategies in the context of English as a Foreign Language (EFL) instruction in Indonesian schools through a cognitive and sociolinguistic approach. It focuses on how Indonesian learners interpret English texts when their linguistic proficiency is limited and when the sociocultural context of the text differs from their local experiences. Employing a qualitative multiple-case study design, the research was conducted in three secondary schools in Bandung Regency. Data were collected through classroom observations, teacher and student interviews, and analysis of students’ reading exercises and written reflections. The analysis integrated the framework of cognitive reading strategies, metacognition, inference, prediction, and self-monitoring, with the sociolinguistic perspective of literacy events to explore the relationship between individual cognitive processes and the social context of learning. The findings reveal that students who actively employ predicting, questioning, and summarizing strategies demonstrate deeper textual understanding. Linking reading materials to local sociocultural contexts, such as environmental issues or community traditions, significantly enhances motivation and engagement. However, a gap remains between teacher-centered instruction and students’ social experiences of meaning-making. The study introduces the Cognitive-Sociolinguistic Reading Framework, which integrates cognitive and sociolinguistic theories to reconceptualize reading comprehension as both a mental and sociocultural practice, contributing theoretical and pedagogical insights for EFL education in Southeast Asia.